2017
DOI: 10.1038/s41598-017-15286-9
|View full text |Cite
|
Sign up to set email alerts
|

Ordered and Disordered Phases in Mo1−xWxS2 Monolayer

Abstract: With special quasirandom structure approach and cluster expansion method combined with first-principle calculations, we explore the structure and electronic properties of monolayer Mo1−xWxS2 alloy with disordered phase and ordered phase. The phase transition from ordered phase to disordered phase is found to happen at 41 K and 43 K for x = 1/3 and x = 2/3, respectively. The band edge of VBM is just related with the composition x, while the band edge of CBM is sensitive to the degree of order, besides the conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
15
1
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 46 publications
7
15
1
1
Order By: Relevance
“…理论上则预测了单层WS 2(1-x) Se 2x 中, 在 Se组分为x=1/3, 1/2和2/3时, 存在有序相 [25] . 之前关于 单层Mo 1-x W x S 2 的有序相和无序相 [26] 的研究发现, Mo [30,31] . 建立 的合金随机结构中, 关于S和Se的关联函数很接近无序 关联函数, 表明采用SQS建立的无序合金结构能很好地 表达实际无序合金的物理特性, 其中, 合金在超胞中的 原子结构如图1所示.…”
Section: 在实验上 扫描透射电子显微镜(Stem)已经观察到了unclassified
“…理论上则预测了单层WS 2(1-x) Se 2x 中, 在 Se组分为x=1/3, 1/2和2/3时, 存在有序相 [25] . 之前关于 单层Mo 1-x W x S 2 的有序相和无序相 [26] 的研究发现, Mo [30,31] . 建立 的合金随机结构中, 关于S和Se的关联函数很接近无序 关联函数, 表明采用SQS建立的无序合金结构能很好地 表达实际无序合金的物理特性, 其中, 合金在超胞中的 原子结构如图1所示.…”
Section: 在实验上 扫描透射电子显微镜(Stem)已经观察到了unclassified
“…Meanwhile, the Jeon group has reported synthesis of MoS X O y by simple CVD method to modulation of band structures of MoS 2 [68]. The Fan group has analyzed other type of ternary TMCs that contain two type of transition metal, in which they have shown different ordered and disordered phases of Mo 1−x W x S 2 monolayer [63].…”
Section: Ternary Transition Metal Chalcogenidesmentioning
confidence: 99%
“…Meanwhile, the Jeon group has reported synthesis of MoSXOy by simple CVD method to modulation of band structures of MoS2 [66]. The Fan group has analyzed other type of ternary TMCs that contain two type of transition metal, in which they have shown different ordered and disordered phases of Mo1−xWxS2 monolayer [61].…”
Section: Ternary Transition Metal Chalcogenidesmentioning
confidence: 99%
“…However, because the transition metal atoms are generally not adsorption sites for layered TMC materials, many works have suggested that the benefit of double cation TMCs may be more attributable to electron density and local field effects, as illustrated in Figure 8a [61].…”
Section: Double Cation Ternary Transition Metal Chalcogenides As Elecmentioning
confidence: 99%